PERAWATAN KULIT ANAK DENGAN DERMATITIS ATOPIK (PERDOSKI, 2022)
Atopic dermatitis (AD) is a very itchy, chronic residual skin inflammation often found in children, thus affecting the quality of life of patients and their families. The pathogenesis of AD is complex and multifactorial, with the primary pathological state being a skin barrier disorder that may induce acute exacerbations. Skincare in AD patients is one of the nonpharmacological measures to repair the skin barrier and prevent a recurrence. The use of mild cleansers, the routine use of moisturizers, the choice of clothing materials, breaking the scratch-itch cycle, and eliminating trigger factors are a series of skincare that have been researched for their clinical benefits in skin barrier disorders. The management of AD patients requires a holistic approach followed by integrating evidence-based skincare and pharmacologic therapy. Improving the pathological skin barrier is the basic principle in managing AD patients. Implementing proper skincare for AD in children needs the help and support of their parents. It is hoped that the adherence, independence, and improvement of the quality of life of patients and their families are expected to be achieved.